Unawareness of hypoglycaemia and inadequate hypoglycaemic counterregulation: no causal relation with diabetic autonomic neuropathy. Issue 6755 (6th October 1990) - Ryder, R E; Owens, D R; Hayes, T M; Ghatei, M A; Bloom, S R
Abstract : OBJECTIVE--To examine the traditional view that unawareness of hypoglycaemia and inadequate hypoglycaemic counterregulation in insulin dependent diabetes mellitus are manifestations of autonomic neuropathy. DESIGN--Perspective assessment of unawareness of hypoglycaemia and detailed assessment of autonomic neuropathy in patients with insulin dependent diabetes according to the adequacy of their hypoglycaemic counterregulation. SETTING--One routine diabetic unit in a university teaching hospital. PATIENTS--23 Patients aged 21-52 with insulin dependent diabetes mellitus (seven with symptoms suggesting autonomic neuropathy, nine with a serious clinical problem with hypoglycaemia, and seven without symptoms of autonomic neuropathy and without problems with hypoglycaemia) and 10 controls with a similar age distribution, without a personal or family history of diabetes. MAIN OUTCOME MEASURES--Presence of autonomic neuropathy as assessed with a test of the longest sympathetic fibres (acetylcholine sweatspot test), a pupil test, and a battery of seven cardiovascular autonomic function tests; adequacy of hypoglycaemic glucose counterregulation during a 40 mU/kg/h insulin infusion test; history of unawareness of hypoglycaemia; and response of plasma pancreatic polypeptide during hypoglycaemia, which depends on an intact and responding autonomic innervation of the pancreas. RESULTS--There was little evidence of autonomic neuropathy in either the 12 diabetic patients with a history of unawareness of hypoglycaemia or the seven patients with inadequate hypoglycaemic counterregulation. By contrast, in all seven patients with clear evidence of autonomic neuropathy there was no history of unawareness of hypoglycaemia and in six out of seven there was adequate hypoglycaemic counterregulation. Unawareness of hypoglycaemia and inadequate hypoglycaemic counterregulation were significantly associated (p less than 0.01). The response of plasma pancreatic polypeptide in the diabetic patients with adequate counterregulation but without autonomic neuropathy was not significantly different from that of the controls (change in plasma pancreatic polypeptide 226.8 v 414 pmol/l). The patients with autonomic neuropathy had a negligible plasma pancreatic polypeptide response (3.7 pmol/l), but this response was also blunted in the patients with inadequate hypoglycaemic counterregulation (72.4 pmol/l) compared with that of the controls (p less than 0.05). CONCLUSIONS--Unawareness of hypoglycaemia and inadequate glucose counterregulation during hypoglycaemia are related to each other but are not due to autonomic neuropathy. The blunted plasma pancreatic polypeptide responses of the patients with inadequate hypoglycaemic counterregulation may reflect diminished autonomic activity consequent upon reduced responsiveness of a central glucoregulatory centre, rather than classical autonomic neuropathy.